Assessing the risk of wild rodents as a potential source of emerging virus infections - Chappell, Joseph Graham (2020)
Rodent-bourne viral zoonoses are a clinically significant group of viruses, however, their prevalence in the United Kingdom is not well-understood. Of particular importance are the Hantaviridae and the Picornaviridae. This thesis describes the screening of rodent tissue collected from four sites in the United Kingdom, as well as sites in Poland and Egypt, for Orthohantaviruses, picornaviruses and orthobornaviruses. Two strains of Tatenale orthohantavirus were detected in field voles (M agrestis) captured at two sites in the United Kingdom. One of these viruses represents a novel strain and was detected in a location with no previous detection of Orthohantaviruses. Additionally, four species of picornaviruses were detected in Mus musculus, Rattus norvegicus and Myodes glareolus. Additional high-throughput sequencing recovered the first complete coding genome of Tatenale virus, which allowed characterisation of the genome and confirmed its status as a novel species. The serological screening of captive non-human primates for evidence of orthohantavirus infection showed evidence of both acute and past infections, which may have implications for the healthcare of these animals, and the conservation efforts of the species. Similarly, there was serological evidence of acute infection in vulnerable human cohorts, which has implications for the healthcare of these individuals and the local population. Finally, high-throughput sequencing of samples from humans with neurological disease of unknown aetiology, recovered evidence of human pegivirus infection in patients with neurological disease, a controversial and emerging topic in clinical virology currently.